(untitled) (Homiletic)
This paper explores the overlapping space between an internal conception of interreligious dialogue and models of conversational preaching and homiletical theology which embrace mutual critical-correlational theological method. At the heart of the paper is a close reading of a sermon focusing on John 5:31–47—preaching much influenced by interreligious hermeneutics. The analysis shows how preaching effectively may address some fundamental principles of interreligious dialogue, for example by offering space for open-minded, respectful, and attentive listening and learning from the religious other, or by encouraging curiosity as well as deep reflection on Christian gospel in the light of gospel resonant of voices from other religious traditions. In the concluding discussion, the implications of this research for the rhetoric of conversational preaching practice are highlighted, and further homiletical-theological reflection on the relationship between preaching and interreligious dialogue is encouraged, not only because it is possible but because it is desirable for Christian preaching and homiletics in particular.